2007
DOI: 10.5642/aliso.20072301.32
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Biogeography of Endemic Festuca (Poaceae) from New Zealand Based on Nuclear (ITS) and Chloroplast (trnL–trnF) Nucleotide Sequences

Abstract: We investigated the phylogenetic relationships of the endemic New Zealand (NZ) species of Festuca (Poaceae, Pooideae) by assessing sequence variation from the nuclear internal transcribed spacers (ITS) and a chloroplast intergenic spacer (trnL-trnF) and by measuring DNA content using flow cytometry. The ITS and trnL-trnF data sets were congruent in showing that the NZ species of Festuca have two origins. One group, containing F. coxii, F. luciarum, F. multinodis, and F. ultramafica, is closely related to Festu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…Furthermore, comparative studies have shown a good capability of trnL intron and trnL-trnF (trnL-F) intergenic spacers, ITS region, and their combinations to resolve grass species [23][24][25][26]. Indel and SNP patterns of the trnL-F intergenic spacer and ITS region have been employed for infrageneric classification and phylogeny study of Chascolytrum and Festuca genera [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, comparative studies have shown a good capability of trnL intron and trnL-trnF (trnL-F) intergenic spacers, ITS region, and their combinations to resolve grass species [23][24][25][26]. Indel and SNP patterns of the trnL-F intergenic spacer and ITS region have been employed for infrageneric classification and phylogeny study of Chascolytrum and Festuca genera [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…, 2001), New Zealand hebes ( Veronica s.l., Plantaginaceae; Meudt & Simpson, 2006; Meudt & Bayly, 2008), Myosotis (Boraginaceae; Winkworth et al. , 2002a), Stylidiaceae (Wagstaff & Wege, 2002), Pachycladon (Brassicaceae; Heenan & Mitchell, 2003), Gentianella (Gentianaceae; Glenny, 2004) and Festuca (Poaceae; Lloyd et al. , 2007), but relatively few of these are suitable for testing the above hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…Luckily the Festuca tussocks provided an interesting story, with two independent origins for the New Zealand species (Figure 2), the two groups of species also being separated by chromosome number and size. I presented this information at a five-yearly international conference on grasses and monocots (Lloyd et al 2003c), and my presentation was later published as a paper in the proceedings of the conference some four years after I had given it (Lloyd et al 2007). At the conference I found that grass taxonomists were a very friendly and collegial bunch, and didn't mind talking to an ecologist with a very limited feel for plant systematics.…”
mentioning
confidence: 99%